2015
DOI: 10.1155/2015/189638
|View full text |Cite
|
Sign up to set email alerts
|

CCL27: Novel Cytokine with Potential Role in Pathogenesis of Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an autoimmune and neurodegenerative disease of unknown etiology. Leukocyte infiltration of brain tissue and the subsequent inflammation, demyelination, axonal damage, and formation of sclerotic plaques is a hallmark of MS. Upregulation of proinflammatory cytokines has been suggested to play an essential role in regulating lymphocyte migration in MS. Here we present data on serum cytokine expression in MS cases. Increased serum levels of IL-17 and IL-23 were observed, suggesting activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…We have previously shown that serum levels of CCL27 are upregulated in subjects with MS (55). CCL27 was two times higher in the serum of acute MS subjects and remained upregulated in the later stages of the disease.…”
Section: Memory Cla+ T Cells In Msmentioning
confidence: 99%
“…We have previously shown that serum levels of CCL27 are upregulated in subjects with MS (55). CCL27 was two times higher in the serum of acute MS subjects and remained upregulated in the later stages of the disease.…”
Section: Memory Cla+ T Cells In Msmentioning
confidence: 99%
“…Among them, RRMS accounts for the majority of patients (about 80%) [87]. The hallmark of MS is leukocyte infiltration of brain tissue and subsequent axonal injury, demyelination inflammation and the formation of sclerosing plaques [54].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown differential activation of cytokines in CSF and serum of MS patients, where the leading role of Th1 lymphocytes in CNS MS pathogenesis was supported. Also, the upregulation of CCL27 was demonstrated in serum and CSF of MS, suggesting the role of this cytokine in neuroinflammation [ 6 ]. Although proinflammatory cytokines are commonly detected in CSF of MS, data remain limited.…”
Section: Introductionmentioning
confidence: 99%